The Aramaic Suzerainty Treaty from Sefire in the Museum of Beirut - Fitzmyer, Jos. A.
Introduction – Transcription – Translation – Commentary – Orthography – Phonology – Morphology – Affinities with the Style of Hittite Treaties - Historical Background.